On The Potential of Dynamic Nuclear Polarization Enhanced Diamonds in Solid‐State and Dissolution 13C NMR Spectroscopy. Issue 17 (19th August 2016) - Bretschneider, Christian O.; Akbey, Ümit; Aussenac, Fabien; Olsen, Greg L.; Feintuch, Akiva; Oschkinat, Hartmut; Frydman, Lucio
Abstract: The front cover artwork is provided by the group of Prof. Lucio Frydman from the Weizmann Institute, in collaboration with Dr. Fabien Aussenac and Profs. Amit Ukbey and Hartmut Oschkinat from Bruker Biospin, Aarhus University and the Leibniz Institute, respectively. The image shows aspects of diamond's dynamic nuclear polarization investigated in this study, in particular their use in dissolution MRI and in solid state magic‐angle‐spinning NMR experiments. Read the full text of the article at10.1002/cphc.201600301 . Abstract : "Nano‐ and micro‐sized diamonds can be hyperpolarized under cryogenic conditions by using nitrogen‐based defects, leading to long‐lived polarizations. However, their subsequent in vivo uses are challenged by solubility problems..…" This and more about the story behind the front cover can be found in the Full Paper at10.1002/cphc.201600301 .